Development of Adphylab in the Geiger-Muller Counter Practicum to Facilitate Science Process Skills - Andri Suherman; Yudi Guntara; Darmawan Kristiaji; Ganesha Antarnusa (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
It is common among students to develop their skills while studying, and it demands educators improve their learning quality. Development of an Advanced Virtual Physics Laboratory (Adphylab) in the Geiger-Muller Counter practicum to facilitate students' science process skills in the Physics Education of Sultan Ageng Tirtayasa University. The research method used is research and development (R&D) with the Rowntree development model. Adphylab in the Geiger muller counter practicum has four menus, including insight, design, time for action, and a summary called WaRa-WiRi which can be accessed easily via the web. The results of the due diligence by material experts at the Adphylab practicum Geiger muller counter obtained a percentage score of 94% with very feasible criteria, and the results of the due diligence by media experts obtained a percentage value of 96% with the very feasible category. The results of the students' limited test responses to Adphylab in the Geiger Muller Counter practicum obtained a score percentage of 90% in the very feasible category.